Blue silicate fluorescent powder with high external quantum efficiency as well as preparation method and application of blue silicate fluorescent powder
By performing high-temperature solid phase reaction under reduced atmosphere, a blue silicate phosphor with high external quantum efficiency was prepared, which solved the problem of lack of high-efficiency blue phosphor in the prior art, and achieved high-light efficiency output under 400 nm purple light excitation, which was suitable for full-spectral LED devices.
Patent Information
- Application Number
- CN202411681178.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, blue phosphor with the main peak of the emission spectrum in the range of 465 to 485 nm and the external quantum efficiency is ≥70% in the prior art, resulting in low light efficiency of full-spectral LED devices packaged in the Vane.
A high-temperature solid phase reaction was carried out under reduced atmosphere by using Ba precursor, Eu precursor, Y precursor and Si precursor to prepare a blue silicate phosphor with high external quantum efficiency. The molecular formula is 0.02≤x≤0.1. The crystal structure of the matrix belongs to the orthogonal crystal system and the space group is Cmcm.
Under the excitation of 400 nm purple light, the main peak of the emission spectrum is within the range of 465-485 nm, and the external quantum efficiency is ≥70%, which significantly improves the light efficiency of the full spectrum LED device.
Smart Images

Figure CN119505903A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fluorescent powders, and in particular to a blue silicate fluorescent powder with high external quantum efficiency and a preparation method and application thereof. Background Art
[0002] Ordinary LEDs, such as those disclosed in Patent Document 1 (A. Debré, G. Whittle, F. Kummer, F. Zwaschka, A. Elens, Fluorescent material mixture, wavelength conversion casting material and light source device, CN100334746C), have a light-emitting principle of using a blue light LED to excite yellow phosphor (wherein the yellow phosphor emits yellow light under the excitation of the blue light emitted by the blue light LED, and the emitted yellow light is mixed with the blue light emitted by the blue light LED that is not completely absorbed by the yellow phosphor to obtain white light); or as disclosed in Patent Document 2 ( Hou Jingshan, Shi Jie, Fang Yongzheng, Jiang Guangxiang, Dong Langping, Wu Jianghua, Liu Yufeng, Zhao Guoying, Zhang Ganghua, a broadband emission green light emitting phosphor and its preparation method and application, disclosed in CN118725854A), a blue light LED excites green phosphor and red phosphor (wherein the green phosphor and the red phosphor emit green light and red light under the excitation of the blue light emitted by the blue light LED, and the emitted green light and red light are mixed with the blue light emitted by the blue light LED that is not completely absorbed by the green phosphor and the red phosphor to obtain white light).
[0003] Ordinary LEDs can meet most daily lighting needs. The average color rendering index (R1-R8) of the spectrum of ordinary LEDs can reach more than 90, but in important indexes such as R9 and R10, its performance may only be The color rendering index of natural light is 100, while the recently proposed full-spectrum lamp (concept) performs very well in color rendering indexes such as R9-R15, with an average of more than 95, which means that it can restore the color of objects more realistically and accurately, with a very small gap with sunlight, and can be used in high-end application fields such as plant lighting, printing, medical testing and museums.
[0004] As disclosed in patent document 3 (Lin Jintian, Chen Lei, Cai Jinlan, Li Chao, full-spectrum phosphor, full-spectrum diode and full-spectrum plant lamp CN108559491B), full-spectrum LED devices are usually excited by purple LEDs, and the phosphors include blue phosphors, green phosphors, red phosphors and infrared phosphors. Among them, the research and development of blue phosphors is more difficult. This is because under normal circumstances, green phosphors, red phosphors and infrared phosphors will have a certain absorption of blue light. And blue phosphors will produce blue light under the excitation of purple LEDs. This means that a considerable part of the blue light generated by blue phosphors under the excitation of purple LEDs will be absorbed by phosphors of other colors. This requires that the quantum efficiency of blue phosphors must be extremely high. Otherwise, the blue light emitted by the blue phosphor is likely to be (largely) absorbed by phosphors of other colors, resulting in a serious lack of blue light in the spectrum of the resulting LED device, and ultimately a full-spectrum LED device cannot be obtained.
[0005] For this purpose, some blue phosphors (structures) have been disclosed. For example, patent document 4 (Yin Liangjun, Dong Juntao, Jian Xian, Zhang Chengui, Chen Guozhang, Wang Chao, Luan Chunhong, A carbon-coated BAM:Eu 2+ Blue phosphor and preparation method thereof, CN104388078A) discloses a carbon-coated BAM:Eu 2+ Blue phosphor. As we all know, BAM:Eu 2+ It is the most common blue phosphor, but its thermal stability is poor. Patent document 4 uses methane to prepare carbon-coated BAM:Eu under high temperature. 2+ The coated phosphor is then subjected to high temperature heat treatment to improve the crystallinity of the phosphor, thereby further improving the BAM:Eu 2+ The luminous intensity of the phosphor is high, and the coated phosphor also has good thermal stability. 2+ There is a problem with blue phosphor, that is, it has strong absorption of ultraviolet light (UV-packaged LED white light devices have problems with rapid aging of the packaging silicone and harmful ultraviolet leakage. Therefore, UV LED-packaged white light LEDs are difficult to apply), but its absorption capacity for purple light is poor, and there are difficulties in developing full-spectrum LED devices for purple light packaging.
[0006] Similarly, non-patent document 1 (Hongyang Zhu, Haibin Yang, Wuyou Fu, Peifen Zhu, Minghui Li, Yixing Li, Yongming Sui, Shikai Liu, Guangtian Zou, The improvement of thermal stability of BaMgAl 10 O17 :Eu 2+ Coated with MgO, Materials Letters, 2008, 62, 4-5: 784-786) The MgO coating method can also improve BAM:Eu 2+ However, as mentioned above, BAM:Eu 2+ There is a problem with blue phosphor, that is, it has strong absorption of ultraviolet light (UV-packaged LED white light devices have problems with rapid aging of the packaging silicone and harmful ultraviolet leakage. Therefore, UV LED-packaged white light LEDs are difficult to apply), but its absorption capacity for purple light is poor, and there are difficulties in developing full-spectrum LED devices for purple light packaging.
[0007] Non-patent document 2 (Jianghui Zheng, Qijin Cheng, Shunqing Wu, Ziquan Guo, Yixi Zhuang, Yijun Lu, Ye Li, Chao Chen, An efficient blue-emitting Sr5(PO4)3Cl:Eu 2+ phosphor for application in near-UV white light-emitting diodes, Materials Letters, J. Mater. Chem. C, 2015, 3, 11219-11227) discloses a chemical composition of Sr5(PO4)3Cl:Eu 2+ But Sr5(PO4)3Cl:Eu 2+ The thermal quenching performance is not as good as BAM:Eu 2+ , and the internal quantum efficiency under 395 nm excitation is only ~80%, and the external quantum efficiency is only ~50%. The low external quantum efficiency leads to the use of Sr5(PO4)3Cl:Eu 2+ Packaged full-spectrum LED devices have low luminous efficacy.
[0008] Non-patent document 3 (Sheng Zhang, Zhendong Hao, Liangliang Zhang, Guo-Hui Pan, Huajun Wu, Xia Zhang, Yongshi Luo, Ligong Zhang, Haifeng Zhao, Jiahua Zhang, Efficient blue-emitting phosphor SrLu2O4:Ce 3+with high thermal stability fornear ultraviolet (~400 nm) LED-chip based white LEDs, Scientific Reports, 2018, 8:10463) discloses a near-ultraviolet excited blue phosphor, whose chemical composition is SrLu2O4:Ce 3+ Under the excitation of 400 nm, the main peak of the emission spectrum of this phosphor is located at 460 nm, the half-height width of the emission spectrum is 90 nm, the internal quantum efficiency is 76%, and the external quantum efficiency is less than 50%. The low external quantum efficiency leads to the use of SrLu2O4:Ce 3+ The luminous efficacy of the packaged full-spectrum LED device is low. In addition, non-patent document 4 (Sheng Zhang, Zhendong Hao, Liangliang Zhang, Guo-Hui Pan, Huajun Wu, Hao Wu, Yongshi Luo, Xingyuan Liu, Hong Zhang, Jiahua Zhang, Observation of a red Ce 3+ center in SrLu2O4:Ce 3+ phosphor and its potential application in temperature sensing, Dalton Trans., 2019, 48, 5263-5270) believes that for Ce 3+ Doped SrLn2O4 (Ln = Y, Lu, Sc, etc.) produces red light emission at about 600 nm under 485 nm blue light excitation. Therefore, as described in Non-Patent Document 3, SrLu2O4:Ce 3+ Under the excitation of 400 nm violet light, blue light reflection will be generated. As described in Non-Patent Document 4, under the excitation of blue light, SrLu2O4:Ce 3+ Will produce red light emission. Therefore, for SrLu2O4:Ce 3 + When the full-spectrum LED device is prepared by using the purple LED package, SrLu2O4:Ce 3+ The multi-color luminescence performance will increase the difficulty of configuring the phosphor color ratio and reduce the packaging efficiency.
[0009] Patent Document 5 (Hou Jingshan, Meng Guichen, Fang Yongzheng, Wu Jianghua, Jiang Guangxiang, Dong Langping, Liu Yufeng, Zhao Guoying, Zhang Ganghua, Lin Yandan, Yang Lei, Zhou Pengcheng, Ma Xianchao, Wang Chuanbing, A cyan fluorescent phosphor for full-spectrum healthy lighting, its preparation method and application, CN118813255A) discloses a cyan fluorescent phosphor with a chemical composition of LiHf2(PO4)3:xEu 2+ (where 0 < x ≤ 0.03), which can be used for full-spectrum healthy lighting. This phosphor is a phosphate-based phosphor and has outstanding advantages such as stable physical and chemical properties, simple preparation, and low cost. However, it should be noted that since this phosphor contains Li, its water resistance is poor, and there is less blue light component in the spectrum, which is difficult for full-spectrum LED devices facing violet packaging.
[0010] Patent Document 6 (Xiong Yonghong, Xiong Caoshui, Wei Deyu, A silicate phosphor and its preparation method, CN102559174A) discloses a silicate phosphor with a chemical general formula of Li2SrSiO4:xEu, where the adjustment range of Eu is: 0.0025 ≤ x ≤ 0.1. Although this phosphor has broadband excitation in the range of 320 nm - 450 nm, simple preparation method, and high energy conversion efficiency, its emission spectrum is located between 470 nm - 570 nm, and the content of blue light component is less. Similarly, Patent Document 7 (Zhou Mingjie, Ma Wenbo, Shi Chaopu, A silicate blue light-emitting material and its preparation method, CN101760195B) also discloses a silicate phosphor with a chemical general formula of , Ag y , where Ln is one of Y, Gd, La, Lu, the value of x is 0 < x ≤ 0.05, and the value of y is 0 < y ≤ 0.005; y is the molar ratio of Ag ions or Ag colloids to silicon. Although this silicate phosphor has good stability and high luminous efficiency, the main peak of its emission spectrum is located at 400 nm, and the luminous color is purple. At the same time, its excitation spectrum is located in the ultraviolet region, which is difficult for full-spectrum LED devices facing violet packaging.
[0011] Nitrides / nitroxides are also important phosphor matrices. Patent Document 8 (Zhang Xiaoling, Lin Xiangyang, Bao Peng, He Guoshu, A nitrogen oxide luminescent material, its preparation method, and a lighting or display light source made therefrom, CN100572498C) discloses a chemical formula of The oxynitride phosphor is a phosphor of the type A, wherein A is one or more of alkali metals, alkaline earth metals, and rare earth metals; B is one or more of the elements of the III-V group and contains at least Si; 0≤x≤1.0; 1.0≤y≤2.0; 1.0≤z≤2.0; 1.0≤w≤3.0. Although the phosphor has the characteristics of wide excitation wavelength range, high efficiency, stability, simple preparation method, easy batch production, and no pollution, the emission wavelength of the phosphor corresponds to blue-green, green, or yellow light, which is not the blue most needed by the full-spectrum LED device of the purple light package.
[0012] Patent document 9 (Xie Mubiao, A blue to cyan color-adjustable phosphor and its preparation method, CN104531143A) discloses a blue to cyan color-adjustable phosphor with the molecular formula Phosphor; where x is the activation ion Ce 3+ Relative alkaline earth metal ion Ca 2+ The molar percentage coefficient is 0.001≤x≤0.10. 3+ As the ion doping concentration increases, the luminescent color of the phosphor gradually changes from blue to cyan. However, it should be pointed out that the material is fluorosilicate, which has poor water resistance and unstable chemical properties, and it is difficult to package it into an LED device.
[0013] Comparative Document 10 (Qu Songnan, Tian Zhen, Zhang Xutao, A carbon nanodot and its preparation method, a carbon nanodot composite material and its preparation method and a light-emitting LED, CN106867528B) discloses a carbon nanodot that can emit cyan light. Similarly, Comparative Document 11 (Wang Hongjia, Zhang Xuejie, Lin Xinying, Tang Anci, Liu Ruxi, Cai Zongliang, Li Yuqun, Chen Jingyi, Tong Hongjun, Quantum dot composite material and its manufacturing method and application, CN107017325B) discloses a modified and protected quantum dot composite material. The quantum dot has the general chemical formula , where 0≤a≤1, 0≤b≤1. Modification protection on the surface of all-inorganic perovskite quantum dots. It should be pointed out that both carbon nanodots and quantum dots have poor stability and are difficult to encapsulate as LED devices.
[0014] In short, there is still a lack of blue phosphors with a main peak of emission spectrum in the range of 465-485 nm and an external quantum efficiency ≥ 70% under 400 nm violet light excitation. The blue luminescent property of (0.02≤x≤0.1, the crystal structure of the phosphor corresponding to the matrix belongs to the orthorhombic system, and the space group is Cmcm) is disclosed for the first time in the present invention. Summary of the invention
[0015] The purpose of the present invention is to solve the above problems in the prior art and provide a blue silicate phosphor with high external quantum efficiency and a preparation method and application thereof. The crystal structure of the material corresponding to the matrix belongs to the orthorhombic system and the space group is Cmcm. 2+ As an activator, under the excitation of 400 nm purple light, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465-485 nm, and the external quantum efficiency is ≥70%.
[0016] Therefore, a first object of the present invention is to provide a blue silicate phosphor with high external quantum efficiency.
[0017] A blue silicate phosphor with high external quantum efficiency, the molecular formula of the material is:
[0018]
[0019] Among them, 0.02≤x≤0.1.
[0020] Preferably, the x may be 0.05.
[0021] The second object of the present invention is to provide a method for preparing a blue silicate phosphor with high external quantum efficiency. The preparation method comprises the following steps: after uniformly mixing a Ba precursor, a Eu precursor, a Y precursor and a Si precursor, performing a high-temperature solid-phase reaction under a reducing atmosphere, a blue silicate phosphor with high external quantum efficiency is obtained.
[0022] Preferably, the molar ratio of Ba to Eu to Y to Si in the Ba precursor, Eu precursor, Y precursor and Si precursor is (1-x):x:2:2, wherein 0.02≤x≤0.1.
[0023] Preferably, the Ba precursor is selected from one or more of Ba carbonate, Ba oxide, Ba oxalate and Ba nitrate; the Eu precursor is selected from one or more of Eu carbonate, Eu oxide, Eu oxalate and Eu nitrate; the Y precursor is selected from one or more of Y carbonate, Y oxide, Y oxalate and Y nitrate; the Si precursor is selected from SiO2.
[0024] Preferably, the purity of the Ba precursor, Eu precursor, Y precursor and Si precursor is not less than 99.5%.
[0025] Preferably, the temperature of the high-temperature solid-phase reaction is 1000-1200° C., the atmosphere is a reducing atmosphere, and the time of the high-temperature solid-phase reaction is 4-10 hours.
[0026] Another object of the present invention is to provide a full-spectrum LED device. The full-spectrum LED device comprises a blue silicate phosphor with high external quantum efficiency (corresponding to the chemical formula , where 0.02≤x≤0.1) and a purple LED chip that can produce light within 380 to 420 nm.
[0027] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0028] According to the implementation method of the present invention, a blue silicate phosphor with high external quantum efficiency can be prepared. The molecular formula of the phosphor is: , where 0.02≤x≤0.1. The crystal structure of the phosphor corresponding to the matrix belongs to the orthorhombic system, and the space group is Cmcm. 2+ As an activator, under the excitation of violet light of 400 nm, the main peak of the emission spectrum is located in the range of 465-485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be used in full-spectrum LED devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is the emission spectrum of the material obtained in Comparative Example 1 under 400 nm excitation.
[0030] Figure 2 It is the emission spectrum of the material obtained in Comparative Example 4 under 400 nm excitation.
[0031] Figure 3 : is the emission spectrum of the material obtained in Example 1 under 400 nm excitation.
[0032] Figure 4 The X-ray diffraction pattern of the material obtained in Example 1 is shown in FIG.
[0033] Figure 5 This is a crystal structure diagram of the material obtained in Example 1.
[0034] Figure 6 This is a spectrum diagram of the full-spectrum LED device obtained in Example 12. DETAILED DESCRIPTION
[0035] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0036] The present invention provides a blue silicate phosphor with high external quantum efficiency, the molecular formula of which is as follows:
[0037]
[0038] Among them, 0.02≤x≤0.1.
[0039] In one embodiment of the present invention, the x is preferably 0.02; in one embodiment of the present invention, the x is preferably 0.03; in one embodiment of the present invention, the x is preferably 0.04; in one embodiment of the present invention, the x is preferably 0.045; in one embodiment of the present invention, the x is preferably 0.05; in one embodiment of the present invention, the x is preferably 0.055; in one embodiment of the present invention, the x is preferably 0.06; in one embodiment of the present invention, the x is preferably 0.07; in one embodiment of the present invention, the x is preferably 0.08; in one embodiment of the present invention, the x is preferably 0.09; in another embodiment of the present invention, the x is preferably 0.1.
[0040] The present invention also provides a method for preparing a blue silicate phosphor with high external quantum efficiency, the steps of which are as follows: mixing a Ba precursor, a Eu precursor, a Y precursor and a Si precursor, and performing a high-temperature solid-phase reaction under a reducing atmosphere to obtain a blue silicate phosphor with high external quantum efficiency.
[0041] In the above steps, the molar ratio of Ba, Eu, Y and Si in the Ba precursor, Eu precursor, Y precursor and Si precursor is , where 0.02≤x≤0.1.
[0042] In the above steps, the Ba precursor can be a compound containing Ba that is well known in the art, and there is no special limitation. In the present invention, it is preferably one or more of Ba carbonate, Ba oxide, Ba oxalate and Ba nitrate, and more preferably Ba carbonate, i.e. BaCO3; the Eu precursor can be selected from one or more of Eu carbonate, Eu oxide, Eu oxalate and Eu nitrate, and more preferably Eu oxide, i.e. Eu2O3; the Y precursor is selected from one or more of Y carbonate, Y oxide, Y oxalate and Y nitrate, and more preferably Y oxide, i.e. Y2O3; the Si precursor is selected from SiO2.
[0043] The purity of the above-mentioned Ba precursor, Eu precursor, Y precursor and Si precursor is not less than 99.5%. The higher the purity, the less impurities in the obtained phosphor.
[0044] In the above steps, the temperature of the high-temperature solid phase is preferably 1000-1200°C, and the atmosphere is a reducing atmosphere; in some embodiments provided by the present invention, the temperature of the high-temperature solid phase is preferably 1100°C; the reducing atmosphere can be a dry atmosphere well known to those skilled in the art, and there is no special limitation. In the present invention, a nitrogen-hydrogen mixed atmosphere with a volume ratio of 9:1 is preferred.
[0045] The high temperature solid phase time in the above steps is preferably 4 to 10 hours, more preferably 5 to 8 hours; in some embodiments provided by the present invention, the high temperature solid phase time is preferably 6 hours.
[0046] The high-temperature solid-phase reaction is preferably carried out in a high-temperature furnace. After the reaction is carried out, the furnace is cooled to room temperature to obtain a blue silicate phosphor with high external quantum efficiency.
[0047] The embodiment of the present invention adopts a high temperature solid phase reaction to successfully prepare a blue silicate phosphor with high external quantum efficiency.
[0048] The present invention also provides a full-spectrum LED device. The full-spectrum LED device at least comprises a molecular formula of (where 0.02≤x≤0.1) a blue silicate phosphor with high external quantum efficiency and a purple LED chip that can generate light within 380-420 nm. The specific production steps include: mixing a blue silicate phosphor with high external quantum efficiency with yellow-green phosphor, orange-red phosphor, dark red phosphor and epoxy resin, applying it to the surface of a purple LED chip that can generate light within the range of 380-420 nm, and then curing it at 150°C for 2 hours to obtain a full-spectrum LED device.
[0049] In order to further illustrate the present invention, a blue silicate phosphor with high external quantum efficiency and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments.
[0050] The reagents used in the following comparative examples and embodiments are all commercially available.
[0051] Comparative Example 1
[0052] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.95:0.05:2:2. After grinding and mixing, the above raw materials are put into a crucible, sintered at 1100℃ for 6h in a high temperature furnace under air atmosphere, and cooled to room temperature with the furnace to obtain the theoretical chemical composition: materials.
[0053] The luminescence performance of the corresponding material in Comparative Example 1 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Figure 1 As shown. Since the reaction is carried out in an air atmosphere, the luminescence of the doped Eu shows Eu 3+ The luminescence corresponding to the ions, Eu was not observed 2+ That is, in the air atmosphere, Eu is not reduced. The material emits a weak, Eu3+ The red light corresponding to the valence state is shown in Table 1. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 2.1%, as shown in Table 1. This external quantum efficiency value is extremely low, indicating that the material has no practical value for encapsulation.
[0054] Comparative Example 2
[0055] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.95:0.05:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 900℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is obtained. materials.
[0056] The luminescence performance of the corresponding material in Comparative Example 2 was analyzed using a fluorescence spectrometer. Since the reaction temperature was too low, the obtained material was in an unsintered powder state, indicating that the reaction to synthesize the target phase did not occur. The obtained material emitted a weak, Eu2O3, and 2O4 emission under 400 nm violet light excitation. 3+ The red light corresponding to the valence state is shown in Table 1. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 0.6%, as shown in Table 1. This external quantum efficiency value is extremely low, indicating that the material has no practical value for encapsulation. A certain temperature is required.
[0057] Comparative Example 3
[0058] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.95:0.05:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1280℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is obtained. materials.
[0059] The luminescence performance of the corresponding material in Comparative Example 3 was analyzed using a fluorescence spectrometer. Due to the high reaction temperature, the obtained material was obviously melted and was in a gray glass state, not a granular polycrystalline powder. The obtained material emitted a weak Eu2O3 luminescence when excited by 400 nm violet light. 3+ The red light corresponding to the valence state is shown in Table 1. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 0.5%, as shown in Table 1. This quantum efficiency value is extremely low, indicating that the material has no practical value for encapsulation. When the temperature exceeds a certain value, it will melt and obtain an amorphous glassy substance that does not emit blue light.
[0060] Comparative Example 4
[0061] The raw materials are SrCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Sr, Eu, Y and Si in SrCO3, Eu2O3, Y2O3 and SiO2 is 0.95:0.05:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is obtained. materials.
[0062] The luminescence performance of the corresponding material in Comparative Example 4 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Figure 2 As shown. Since the reaction is carried out in a reducing atmosphere, the luminescence of the doped Eu 2+ Luminescence (broad-spectrum emission), that is, Eu in The material emits a weak green light under 400 nm violet light excitation, as shown in Table 1. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 10.4%, as shown in Table 1. This quantum efficiency value is extremely low, indicating that the material has no practical value for packaging. The results of X-ray diffraction show that and have the same crystal structure, but for For blue phosphors used in full-spectrum LED device packaging, their emission spectrum is green. and Has the same crystal structure, but contains Sr The sample is not suitable.
[0063] Comparative Example 5
[0064] The raw materials are CaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ca, Eu, Y and Si in CaCO3, Eu2O3, Y2O3 and SiO2 is 0.95:0.05:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is obtained. materials.
[0065] The luminescence performance of the material obtained in Comparative Example 5 was analyzed using a fluorescence spectrometer. The obtained sample was a loose powder with a gray surface color. The obtained material emitted a weak, Eu2O3, and 2O4 emission when excited by 400 nm violet light. 3+The red light corresponding to the valence state is shown in Table 1. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 1.5%, as shown in Table 1. This quantum efficiency value is extremely low, indicating that the material has no practical value for packaging. The results of X-ray diffraction show that the nominal composition is The actual chemical composition of the sample is and unreacted Y2O3. Obviously, for blue phosphors used in full-spectrum LED device packaging, the nominal composition is The sample is not suitable.
[0066] Comparative Example 6
[0067] The raw materials are BaCO3, SrCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Sr, Eu, Y and Si in BaCO3, SrCO3, Eu2O3, Y2O3 and SiO2 is 0.5:0.45:0.05:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100°C for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. The theoretical chemical composition is obtained. materials.
[0068] The luminescence performance of the corresponding material in Comparative Example 6 was analyzed using a fluorescence spectrometer. Since the reaction was carried out in a reducing atmosphere, the luminescence performance of the doped Eu was Eu 2+ Luminescence (broad-spectrum emission), that is, Eu in The material emits a weak cyan light under 400 nm violet light excitation, as shown in Table 1. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 23.8%, as shown in Table 1. The low quantum efficiency value indicates that the material has no practical value for packaging. The results of X-ray diffraction show that and have the same crystal structure, but for For blue phosphors used in full-spectrum LED device packaging, its emission spectrum is cyan. and Has the same crystal structure, but contains Sr The sample is not suitable.
[0069] Comparative Example 7
[0070] The raw materials are BaCO3, Eu2O3, La2O3 and SiO2. The molar ratio of Ba, Eu, La and Si in BaCO3, Eu2O3, La2O3 and SiO2 is 0.95:0.05:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is obtained. materials.
[0071] The luminescence performance of the corresponding material in Comparative Example 7 was analyzed using a fluorescence spectrometer. When La completely replaces Y, the nominal composition obtained is The sample emits weak Eu 3+ The red light corresponding to the valence state is shown in Table 1. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 3.7%, as shown in Table 1. This quantum efficiency value is extremely low, indicating that the material has no practical value for packaging. The results of X-ray diffraction show that and They have the same crystal structure. However, they (all) contain La and have a nominal composition of The sample does not emit blue light, and Eu should occupy the La crystallographic lattice, which eventually appears as Eu 3 + valence state, thereby emitting Eu 3+ The valence state characteristic is weak red light. Obviously, for blue phosphors used in full-spectrum LED device packaging, and Same crystal structure, but (all) containing La The sample is not suitable.
[0072] Comparative Example 8
[0073] The raw materials are BaCO3, Eu2O3, Sc2O3 and SiO2. The molar ratio of Ba, Eu, Sc and Si in BaCO3, Eu2O3, Sc2O3 and SiO2 is 0.95:0.05:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the theoretical chemical composition is obtained. materials.
[0074] The luminescence performance of the corresponding materials in Comparative Example 8 was analyzed using a fluorescence spectrometer. When Sc completely replaces Y, the nominal composition obtained is The sample emits a weak cyan light under 400 nm violet light excitation, as shown in Table 1. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 6.6%, as shown in Table 1. This quantum efficiency value is extremely low, indicating that the material has no practical value for packaging. The results of X-ray diffraction show that the nominal composition The sample contained trace amounts of and unreacted Sc2O3 and SiO2. 2+ Doped It will produce cyan light, and the main peak of the emission spectrum is at 500 nm, not blue light. Obviously, for blue phosphors used in full-spectrum LED device packaging, the nominal composition is The sample is not suitable.
[0075] Comparative Example 9
[0076] The raw materials are BaCO3, Eu2O3, Y2O3, La2O3 and SiO2. The molar ratio of Ba, Eu, Y, La and Si in BaCO3, Eu2O3, Y2O3, La2O3 and SiO2 is 0.95:0.05:1:1:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100°C for 6 hours in a high-temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. The theoretical chemical composition is obtained. materials.
[0077] The luminescence performance of the corresponding material in Comparative Example 9 was analyzed using a fluorescence spectrometer. When La partially replaced Y, the nominal composition of The sample emits weak Eu 3+ The red light corresponding to the valence state is shown in Table 1. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 2.7%, as shown in Table 1. This quantum efficiency value is extremely low, indicating that the material has no practical value for encapsulation. The results of X-ray diffraction show that the matrix With matrix They have the same crystal structure. However, the nominal composition of La and Y is The sample does not emit blue light; and Eu should occupy the La crystallographic lattice, which will eventually appear as Eu 3+ valence state, thereby emitting Eu 3+ The valence state characteristic is weak red light. Obviously, for blue phosphors used in full-spectrum LED device packaging, and Has the same crystal structure, but contains some La The sample is not suitable.
[0078] Comparative Example 10
[0079] The raw materials are BaCO3, Eu2O3, Y2O3, Sc2O3 and SiO2. The molar ratio of Ba, Eu, Y, Sc and Si in BaCO3, Eu2O3, Y2O3, Sc2O3 and SiO2 is 0.95:0.05:1:1:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100°C for 6 hours in a high-temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. The theoretical chemical composition is obtained. materials.
[0080] The luminescence performance of the corresponding material in Comparative Example 10 was analyzed using a fluorescence spectrometer. When Sc is partially substituted for Y, the nominal composition obtained is The sample emits a weak cyan light under 400 nm violet light excitation, as shown in Table 1. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 3.5%, as shown in Table 1. This quantum efficiency value is extremely low, indicating that the material has no practical value for packaging. The results of X-ray diffraction show that the nominal composition The sample contained trace amounts of and unreacted Y2O3, Sc2O3 and SiO2. 2+ Doped It will produce cyan light, and the main peak of the emission spectrum is at 499 nm, not blue light. Obviously, for blue phosphors used in full-spectrum LED device packaging, the nominal composition is The sample is not suitable.
[0081] Example 1
[0082] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.98:0.02:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the crucible is cooled to room temperature to obtain a material with the chemical composition of of phosphor.
[0083] The corresponding phosphor in Example 1 was analyzed using a fluorescence spectrometer to obtain its emission spectrum, as shown in FIG. Figure 3As shown. When the material is excited by 400 nm violet light, the main peak of the emission spectrum is located at 465 nm, and the main peak of the corresponding excitation spectrum is located at ~400 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 73.7%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high practical value for packaging. It can be seen that Example 1 is a blue silicate phosphor with high external quantum efficiency. When excited by 400 nm violet light, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be used in full-spectrum LED devices. The structure of the material obtained in Example 1 was subjected to X-ray diffraction analysis using an X-ray diffractometer, and its diffraction pattern is shown as follows. Figure 4 As shown; through single crystal diffraction, combined with the data of powder structure refinement, it is shown that the crystal structure of this material (matrix) belongs to the orthorhombic system, and the space group is Cmcm. Figure 5 A diagram of the crystal structure of the material (matrix) is given.
[0084] Example 2
[0085] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.97:0.03:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the crucible is cooled to room temperature to obtain a material with the chemical composition of of phosphor.
[0086] The corresponding phosphor in Example 2 was analyzed using a fluorescence spectrometer. Under 400 nm violet light excitation, the main peak of the emission spectrum of the material is located at 466 nm, and the main peak of the corresponding excitation spectrum is located at ~400 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 73.5%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. It can be seen that Example 2 is a blue silicate phosphor with high external quantum efficiency. Under 400 nm violet light excitation, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be applied to full-spectrum LED devices.
[0087] Example 3
[0088] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.96:0.04:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the mixture is cooled to room temperature to obtain a product with the chemical composition of of phosphor.
[0089] The corresponding phosphor in Example 3 was analyzed using a fluorescence spectrometer. Under 400 nm violet light excitation, the main peak of the emission spectrum of the material is located at 468 nm, and the main peak of the corresponding excitation spectrum is located at ~400 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 75.4%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. It can be seen that Example 3 is a blue silicate phosphor with high external quantum efficiency. Under 400 nm violet light excitation, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be applied to full-spectrum LED devices.
[0090] Example 4
[0091] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.955:0.045:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100°C for 6 hours in a high-temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the crucible is cooled to room temperature to obtain a material with the chemical composition of of phosphor.
[0092] The corresponding phosphor in Example 4 was analyzed using a fluorescence spectrometer. Under 400 nm violet light excitation, the main peak of the emission spectrum of the material is located at 469 nm, and the main peak of the corresponding excitation spectrum is located at ~400 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 76.1%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. It can be seen that Example 4 is a blue silicate phosphor with high external quantum efficiency. Under 400 nm violet light excitation, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be applied to full-spectrum LED devices.
[0093] Example 5
[0094] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.95:0.05:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the crucible is cooled to room temperature to obtain a material with the chemical composition of of phosphor.
[0095] The corresponding phosphor in Example 5 was analyzed using a fluorescence spectrometer. Under 400 nm violet light excitation, the main peak of the emission spectrum of the material is located at 472 nm, and the main peak of the corresponding excitation spectrum is located at ~400 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 81.1%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. It can be seen that Example 5 is a blue silicate phosphor with high external quantum efficiency. Under 400 nm violet light excitation, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be applied to full-spectrum LED devices.
[0096] Example 6
[0097] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.945:0.055:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the crucible is cooled to room temperature to obtain a material with the chemical composition of of phosphor.
[0098] The corresponding phosphor in Example 6 was analyzed using a fluorescence spectrometer. Under 400 nm violet light excitation, the main peak of the emission spectrum of the material is located at 474 nm, and the main peak of the corresponding excitation spectrum is located at ~400 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 79.9%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. It can be seen that Example 6 is a blue silicate phosphor with high external quantum efficiency. Under 400 nm violet light excitation, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be applied to full-spectrum LED devices.
[0099] Example 7
[0100] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.94:0.06:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the crucible is cooled to room temperature to obtain a material with the chemical composition of of phosphor.
[0101] The corresponding phosphor in Example 7 was analyzed using a fluorescence spectrometer. Under 400 nm violet light excitation, the main peak of the emission spectrum of the material is located at 479 nm, and the main peak of the corresponding excitation spectrum is located at ~400 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 76.3%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. It can be seen that Example 7 is a blue silicate phosphor with high external quantum efficiency. Under 400 nm violet light excitation, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be applied to full-spectrum LED devices.
[0102] Example 8
[0103] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.93:0.07:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the crucible is cooled to room temperature to obtain a material with the chemical composition of of phosphor.
[0104] The corresponding phosphor in Example 8 was analyzed using a fluorescence spectrometer. Under 400 nm violet light excitation, the main peak of the emission spectrum of the material is located at 480 nm, and the main peak of the corresponding excitation spectrum is located at ~400 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 75.2%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. It can be seen that Example 8 is a blue silicate phosphor with high external quantum efficiency. Under 400 nm violet light excitation, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be applied to full-spectrum LED devices.
[0105] Example 9
[0106] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.92:0.08:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the crucible is cooled to room temperature to obtain a material with the chemical composition of of phosphor.
[0107] The corresponding phosphor in Example 9 was analyzed using a fluorescence spectrometer. Under 400 nm violet light excitation, the main peak of the emission spectrum of the material is located at 483 nm, and the main peak of the corresponding excitation spectrum is located at ~400 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 73.3%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. It can be seen that Example 9 is a blue silicate phosphor with high external quantum efficiency. Under 400 nm violet light excitation, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be applied to full-spectrum LED devices.
[0108] Example 10
[0109] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.91:0.09:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the crucible is cooled to room temperature to obtain a material with the chemical composition of of phosphor.
[0110] The corresponding phosphor in Example 10 was analyzed using a fluorescence spectrometer. Under 400 nm violet light excitation, the main peak of the emission spectrum of the material is located at 483 nm, and the main peak of the corresponding excitation spectrum is located at ~400 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 72.1%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. It can be seen that Example 10 is a blue silicate phosphor with high external quantum efficiency. Under 400 nm violet light excitation, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be applied to full-spectrum LED devices.
[0111] Embodiment 11
[0112] The raw materials are BaCO3, Eu2O3, Y2O3 and SiO2. The molar ratio of Ba, Eu, Y and Si in BaCO3, Eu2O3, Y2O3 and SiO2 is 0.9:0.1:2:2. After grinding and mixing, the above raw materials are put into a crucible and sintered at 1100℃ for 6h in a high temperature furnace under a nitrogen and hydrogen mixed atmosphere with a volume ratio of 9:1. Then, the crucible is cooled to room temperature to obtain a material with the chemical composition of of phosphor.
[0113] The corresponding phosphor in Example 11 was analyzed using a fluorescence spectrometer. Under 400 nm violet light excitation, the main peak of the emission spectrum of the material is located at 485 nm, and the main peak of the corresponding excitation spectrum is located at ~400 nm. The quantum efficiency of the material was tested using a quantum efficiency tester, and its external quantum efficiency was 70.6%, as shown in Table 1. The quantum efficiency value is extremely high, indicating that the material has extremely high packaging practical value. It can be seen that Example 11 is a blue silicate phosphor with high external quantum efficiency. Under 400 nm violet light excitation, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%, so that the phosphor can be applied to full-spectrum LED devices.
[0114] Table 1 Luminescent properties of materials corresponding to comparative examples and examples
[0115]
[0116] Example 12
[0117] Select the synthesized Blue phosphor combined Yellow-green phosphor, Orange-red phosphor, Deep red phosphor is mixed with epoxy resin in a mass ratio of 1:0.32:0.44:0.51:10, and the mixture is coated on a purple LED with a main peak of emission spectrum at 400 nm, encapsulated, and then cured at 150°C for 2 hours to obtain a full-spectrum LED device with a color rendering index of 97.9. The spectrum of the device is shown in Figure 6 shown.
[0118] The above embodiments are only used to illustrate the implementation methods of the present invention and to explain the technical features of the present invention, and are not used to limit the protection scope of the present invention. Any changes or equivalent arrangements that can be easily completed by a person familiar with this technology belong to the scope claimed by the present invention, and the scope of protection of the present invention shall be subject to the claims.
Claims
1. A blue silicate phosphor with high external quantum efficiency, characterized in that: The molecular formula of the blue silicate phosphor with high external quantum efficiency is , wherein 0.02≤x≤0.1; the crystal structure of the corresponding matrix of the blue silicate phosphor with high external quantum efficiency belongs to the orthorhombic system, and the space group is Cmcm; under the excitation of 400 nm violet light, the main peak of the emission spectrum of the blue silicate phosphor with high external quantum efficiency is located in the range of 465 to 485 nm, and the external quantum efficiency is ≥70%.
2. A blue silicate phosphor with high external quantum efficiency as claimed in claim 1, characterized in that: The x is 0.
05.
3. A method for preparing a blue silicate phosphor with high external quantum efficiency according to any one of claims 1 to 2, characterized in that: A Ba precursor, a Eu precursor, a Y precursor and a Si precursor are mixed, and a high-temperature solid-phase reaction is carried out in a reducing atmosphere to obtain a blue silicate phosphor with high external quantum efficiency.
4. The method for preparing a blue silicate phosphor with high external quantum efficiency as claimed in claim 3, characterized in that: The molar ratio of Ba, Eu, Y and Si in the Ba precursor, Eu precursor, Y precursor and Si precursor is , where 0.02≤x≤0.
1.
5. The method for preparing a blue silicate phosphor with high external quantum efficiency as claimed in claim 3, characterized in that: The temperature of the high temperature solid phase reaction is 1000-1200° C., and the time of the high temperature solid phase reaction is 4-10 hours.
6. The method for preparing a blue silicate phosphor with high external quantum efficiency as claimed in claim 3, characterized in that: The Ba precursor is selected from one or more of Ba carbonate, Ba oxide, Ba oxalate and Ba nitrate; the Eu precursor is selected from one or more of Eu carbonate, Eu oxide, Eu oxalate and Eu nitrate; the Y precursor is selected from one or more of Y carbonate, Y oxide, Y oxalate and Y nitrate; the Si precursor is selected from SiO2.
7. Use of a blue silicate phosphor with high external quantum efficiency as claimed in any one of claims 1 to 2 or a blue silicate phosphor with high external quantum efficiency obtained by the preparation method of any one of claims 3 to 6, characterized in that: Used to prepare full-spectrum LED devices.
8. A full-spectrum LED device, characterized in that: The invention comprises a blue silicate phosphor with high external quantum efficiency as described in any one of claims 1 to 2 or a blue silicate phosphor with high external quantum efficiency obtained by the preparation method of any one of claims 3 to 6.
9. A full-spectrum LED device as claimed in claim 8, characterized in that: It also includes a purple LED chip that can emit light with a peak wavelength within 380 to 420 nm.